THE ROLE OF WORK IN PRISON AND ITS IMPACT ON THE REHABILITATION IN MODERN PENITENTIARY SYSTEMS - Bardhi, Krenar (E-Journal VFU, 2026)
This article analyzes the role of prison work as a criminological mechanism in the rehabilitation of inmates and the reduction of recidivism in modern penitentiary sysems. Drawing on contemporary criminological literature and evidence-based models, the study examines the interaction between structured activities, psychological interventions, and institutional factors. Through a theoretical analysis and a case study at IEVP Peqin, as well as an empirical survey of 80 inmates, the paper highlights that the effectiveness of prison work depends on implementation, staff training, and the structure of rehabilitation programs.